Adjusting to BRICs in Glass Houses: Replacing Obsolete Institutions and Business Models. (19th December 2012) - Aggarwal, Raj
Abstract Global adjustment to the rise of the BRIC and other emerging economies is an important challenge for firms in the advanced economies. Emerging market firms increasingly trade and invest globally while monetary imbalances continue to rise and hobble advanced economy firms. Advanced country firms feel like they live in glass houses as the tectonic forces of technology, demographics, globalization, sustainability, and climate change force obsolescence in their business models. In this article, this overseas projection of economic power by the rising new economies is illustrated by the Indian and Chinese overseas economic expansion focused on Africa. This analysis shows that noneconomic state‐driven entities are likely to be a significant part of the rise of South‐South economic trade and investment flows and it poses theoretical and practical problems for existing market‐based economic and geopolitical institutions. Global adjustment to these new realities is also challenging as existing multilateral institutions seem to be inadequate. These changes in the global environment have significant implications for policy makers and managers of global companies. © 2013 Wiley Periodicals, Inc.